Beyond the Work Product: A Guide to Relationship-Driven Transactional Lawyering - Landy, Rachel (American Bar Association, 2021)
Beyond the Work Product will prepare business attorneys (and particularly law students and new attorneys) for a successful law practice by providing a framework for effective and efficient lawyering. It emphasizes building relationships and trust with clients so that, despite the existence of less costly alternatives, they will keep coming back for more.The approach is process-focused rather than outcome-focused; it emphasizes every step of the lawyering process, not simply delivering the best work product possible. Whether you are at a big firm, a small firm, or a solo practice, approaching lawyering as a relationship-driven job will help you build a sustainable practice and even increase your enjoyment of your work.